“Yerba mate” extract in anticorrosive paints to protect SAE 1010 steel - Silvestri, Yaco (2018)
The aim of this work was to formulate, prepare and test epoxy water-borne paints with yerba mate (Ilex paraguariensis) extract. The extract was prepared by stirring yerba mate leaves in distilled water during 24 h. The supernatant was heated up to 75ºC for 15 min in a rotavapor. The concentrated extract was dried in laboratory conditions overnight.